Le traduzioni di Rimbaud in Italia - Giovine, Sara (Incontri. Rivista europea di studi italiani, 2018)
Rimbaud translations in Italy This essay intends to outline a balance of the critical fortune of Arthur Rimbaud inItaly through the history of his translation. The study, which is based on the electronic data-base TRALYT – Translation and Lyrical Tradition between Italy and France (19th - 21st Century), under development at the University of Padua, intends to offer a complete bibliographic overview of the translations of Rimbaud’spoems, published in Italy between the end of the 19th century and the second decade of the new millennium. Within the history of these Italian translations, itidentifies six main seasons: the first concerns the twenty years that extend from the late 19th century to the early 1920s, which sees the first diffusion of the works ofthe French poet in our country; the second coincides with the fifteen years that goes from the beginning of the 1930s to the mid-1940s, with the first translation of hermetic poets; the third one is placed in the post-war period, between the second half of the 1940s and the beginning of the 1950s; the fourth embraces the decade that goes from the celebration of the centenary of the birth of Rimbaud in 1954, tothe first complete Italian edition of his works in 1964; the fifth is related to the 1970s and 1980s, marked by the publication of the full edition of Rimbaud at the main publishing houses; finally, the sixth season involves the period from the last decade of the 20th century to the present day.